Differential social distance and confidence in the police. (September 2015) - Lee, Joongyeup; Lim, Hyeyoung; Lee, Hoon
Despite the emphasis on community relations in recent developments in policing, the importance of social distance between citizens and the police has not been explored. In the current study, we examine the effect of social distance on public attitudes toward the police using data from a sample of college students in a mid-sized State university. The findings from path analysis suggest that students' familiarity with and interest in the police promote confidence in the police, even when controlling for variables such as negative contacts and exposure to media coverage of police misconduct. The findings are discussed in reference to recent policing initiatives that are designed to facilitate amicable citizen–police relationships.